2016
DOI: 10.1016/j.molcatb.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable solid-phase biocatalyst with improved stability by sol–gel entrapment of β-d-galactosidase

Abstract: *Graphical Abstract (for review) Highlights:Alkyl substituted silane precursors were used for entrapment of β-D-galactosidaseThe highest activity in optimized immobilization conditions was 84 μmol minThe entrapped β-D-galactosidase demonstrated increased pH and temperature stabilityMore than 60% residual activity was preserved after 5 reutilizations transmission electron microscopy, scanning electron microscopy, fluorescence confocal 2 microscopy, and porosity measurement. The biocatalyst was successfully reu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…3 ; Additional file 1 : Figure S2) was studied in the range 5.5 < pH < 8.5 using a McIlvaine’s buffer (0.1 M citric acid and 0.2 M Na 2 HPO 4 at different ratios). Consistent with previous studies [ 26 ] the activity of free β-gal was observed to peak at ~pH 7. Upon adsorption the enzymatic activity decreases drastically by a factor of 60 at pH ≤ 7.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…3 ; Additional file 1 : Figure S2) was studied in the range 5.5 < pH < 8.5 using a McIlvaine’s buffer (0.1 M citric acid and 0.2 M Na 2 HPO 4 at different ratios). Consistent with previous studies [ 26 ] the activity of free β-gal was observed to peak at ~pH 7. Upon adsorption the enzymatic activity decreases drastically by a factor of 60 at pH ≤ 7.…”
Section: Resultssupporting
confidence: 93%
“…Such nanoparticle agglomerates are used in the present study to evaluate the impact of enzyme adsorption on its catalytic activity. For this purpose we selected β-galactosidase (β-gal) which has been used in previous model studies on enzyme immobilization at metal oxide nanomaterials [ 21 26 ]. Here we report the first qualitative and quantitative results obtained for enzyme adsorption using FT-IR spectroscopy and light scattering techniques and discuss challenges and pitfalls which typically arise during the evaluation of enzymatic activity changes between free and adsorbed proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial research efforts have been made in developing an adequate immobilized b-galactosidase preparation. Different immobilization methods (adsorption, covalent binding, entrapment and cross-linking), and various support materials, including natural [16][17][18] and synthetic polymers 10,[19][20][21] or inorganic materials, [22][23][24][25] have been tested for immobilization of b-galactosidase. Recently, a great deal of interest was drawn to immobilization of industrially important enzymes onto nanoscale materials for improved catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, it may be very useful to prevent enzyme subunit dissociation of multimeric enzymes (Fernandez‐Lafuente ). Entrapment of enzymes is a simple technique of enzyme immobilization (Reetz and others ; Katiyar and Ali ; Bibi and others ; Biró and others ). However, it may hardly improve enzyme properties (exception is made on multimeric enzymes, preventing enzyme dissociation, or generation of favorable enzyme environments), and it tends to be not very simple to be performed at a large scale.…”
Section: Improving Proteases For Biotechnology Applicationsmentioning
confidence: 99%